PENGEMBANGAN EKOSISTEM EKONOMI DIGITAL DI YOGYAKARTA: PELUANG, TANTANGAN, DAN INISIATIF PEMERINTAH DAERAH - Ratih Latifah Anggraini; Fahlevvi, Mohammad Rezza (LPPM Universitas Dhyana Pura, 2025)
Digital technology is rapidly evolving, bringing changes to all aspects of life. Governments are required to be capable of responding to these technological changes through agile governance in order to meet public needs. The Special Region of Yogyakarta (DIY) has been designated as a national pilot project for a smart province. Its high internet penetration rate and strong digital literacy index make DIY a strategic area for developing a digital ecosystem, supported by its local potential in culture, tourism, and education. This research aims to analyze the development of the digital economy ecosystem by the DIY regional government and to identify the opportunities and challenges involved. The study employs a descriptive qualitative approach and uses De-Leon’s (2019) theory of digital ecosystem development as its analytical framework. The findings show that the DIY government has made significant efforts to develop the digital economy ecosystem through the establishment of the Sibakul Jogja digital MSME platform, the development of digital infrastructure, the implementation of the Jogja Smart Province roadmap policy, and cross-sectoral collaboration. Key opportunities for ecosystem development include the presence of digital communities, a strong talent pool in the IT sector from leading universities, and good digital accessibility. The main challenge lies in the unequal distribution of digital marketing skills among MSME actors. The study concludes that the development of the digital ecosystem in DIY has shown positive results and can serve as a model for adaptive and inclusive digital economy governance.